Genomic Analysis and Comparison of Pakistani Camels (Camelus dromedarius) by Prion Gene - Hussain, Tanveer; Musthafa, Muneeb; Babar, Masroor Ellahi; Marikar, Faiz; Hussain, Fiaz; Khan, Saeed Akram; Sherzada, Shahid; Ali, Ahmad (Acta Scientiae Veterinariae, 2017)
Background: In many parts of the Old World, domesticated camels (genus - Camelus) are an essential resource, providing food, labor, commodities, and sport to millions of people Of the three extent species, two have been domesticated (singlehumped dromedarius, Camelus dromedarius, and two humped Bactrian camels Camelus bactrianus) and one remains wild (two-humped wild Bactrian camels Camelus ferus). All three species possess a variety adaptations to harsh desert conditions, including mechanisms to tolerate of extreme temperatures, dehydration, and sandy terrain. People residing in harsh climate zones of the world are being benefitted by raising camels in terms of draft, milk, meat, hides and wool from centuries. There are different breeds of dromedary camels distributed in various parts of Pakistan; however there have been scarcity of research work on camels in Pakistan. Identification of novel link between Camel breeders with fatal neurodegenerative disorders is presence or not can be detect by a Prion gene and it was not carried out in Pakistan soil to date. Prion diseases which are a group of fatal neurodegenerative disorders affect both animals and humans. It is believed that the prions are infectious agents responsible for transmissible spongiform encephalopathies. In this study we report the first study on Prion protein gene in dromedary camels of Pakistan. Material, Methods & Results: Genes are the blueprint of life and determine the functional aspects of cellular mechanisms. Genomic DNA of the enrolled blood samples was extracted using the Nucleospin® DNA extraction kit. Genomic DNA was run on Agarose gel electrophoresis, checked the Genomic DNA quality and amplified using prion region specific primer pair. Prion protein gene was amplified (770 bp) in 35 individuals of seven dromedary camel breeds from the province Balochistan and Punjab of Pakistan. Samples having required fragment size were selected and sent for sequencing through Sanger Sequencing. All the sequences were aligned through multiple sequence alignment and edited using Codon Code aligner and explored for phylogenetic analysis. A portion of 667 bp was finally selected for phylogenetic analysis of dromedary camels from Pakistan with 61 different mammalian species (drawn from GenBank) that revealed five different clades. We found 99.9% nucleotide sequence similarities among Dromedary camels (Germany), Dromedary camels (Iran), and Dromedary camels (Pakistan). We observed deletion in dromedary camels in codon region 66-69 except wild Bactrian camels that might be the causative factor for Prion protein gene resistance in camels. The Neighbor-Joining method with bootstrap analysis of 1000 replicates was used to draw phylogenetic tree. Discussion: This study documents the presence of 14 PrP polymorphisms and shows the relationship between different camel breeds. The deletion had not previously been examined PrP allelic variation, and was found to segregate in these breeds. However, additional data are necessary to demonstrate PrP and genetic approach will be ideal for the future studies and, more investigations are necessary to demonstrate PrP genetic resistance in camels. The utility of these techniques in identifying Prion genes and selecting superior animals and culling the weak animals and making them parents of the next generation that will lead to producing more meat and milk with fewer animals are well discussed and by slaughtering of high Prion incidence will eliminate human animal fatal neurodegenerative disorders.